An Interview with Antti Juvonen: Creativity, Talent and Giftedness in Finland - Shaughnessy, Michael; Beaudet, Kaitlyn (European Scientific Journal, ESJ, 2021)
- In your opinion, how well does Finland teach, mentor, coach and help gifted and talented and creative students? I suppose you mean the school education context. I am afraid that gifted, talented and creative students have been almost forgotten in our Finnish school system. I believe that the only thing that is currently being done for gifted, talented and creative pupils is differentiating upwards, which means in practice, offering them some extra exercises. This is mostly because in Finland we have a system where pupils with special needs are put in normal classes with other pupils. It is called inclusion. Pupils with special needs have been supported with a so called “three step support” since 2011. The first step is general support which the teacher offers with individual pedagogical solutions. The second step is aimed for pupils with long-lasting wider needs for support. It is called intensified support. If this does not help the pupil, the system offers specific support which can be offered after quite comprehensive studies are made by psychologists and other specialists. The idea of this model was to help all pupils to get as good and comprehensive an education as possible. What went wrong was that the cities and especially small towns, did not hire enough helping personnel to support the pupils with special needs. This causes big challenges to class teachers who are put in a position of a special education teacher: they have to take care of pupils with special needs, but at the same time they should be able to teach the rest of the class with normal level pupils and the gifted, talented and creative pupils. Of course, the pupils with special needs take most of their time, which means that the others must try to learn at least the minimum of the curriculum’s requirements. The most gifted often become frustrated and start inventing activities which also disturb the classroom action and atmosphere. This happens because they are bored and do not get any response or activation or response for their innovativeness or special gifts. So, as a whole I see the situation quite poor from the point of view of those groups mentioned.